Characterization of Virologic Rebound Following Nirmatrelvir-Ritonavir Treatment for Coronavirus Disease 2019 (COVID-19). (15th July 2022) - Boucau, Julie; Uddin, Rockib; Marino, Caitlin; Regan, James; Flynn, James P; Choudhary, Manish C; Chen, Geoffrey; Stuckwisch, Ashley M; Mathews, Josh; Liew, May Y; Singh, Arshdeep; Reynolds, Zahra; et al.
Abstract: We enrolled 7 individuals with recurrent symptoms or antigen test conversion following nirmatrelvir-ritonavir treatment. High viral loads (median 6.1 log10 copies/mL) were detected after rebound for a median of 17 days after initial diagnosis. Three had culturable virus for up to 16 days after initial diagnosis. No known resistance-associated mutations were identified.